Constructionism, knowledge and reality: a critical appraisal from Social Psychology - Sandoval Moya, Juan (MAD, 2010)
This article discusses the perspective of "constructionism", from the point of view of the social psychology. It presents the main arguments and criticisms that have been made to this position.